2000
DOI: 10.1111/j.1550-7408.2000.tb00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the Small Subunit Ribosomal RNA of Marteilia.refringens Validates the Existence of Phylum Paramyxea (Desportes and Perkins, 1990)1

Abstract: Marteilia refringens is recognized as one of the most significant pathogens of bivalve molluscs. The nucleotide sequence of the small subunit ribosomal RNA gene of Marteilia refringens is used to elucidate the phylogenetic position of the phylum Paramyxea. Genomic DNA was extracted from sporangia of Marteilia, purified from infected blue mussels, Mytilus edulis, and flat oysters, Ostrea edulis. The sequences obtained from Marteilia species purified from both oysters and mussels were identical. The sequence ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 26 publications
4
33
0
Order By: Relevance
“…Examples include the phylogenetic position of Marteilia refringens (Berthe et al 2000), Pfiesteria shumwayae (Litaker et al 2005), and the phylogenetic synonymization of Perkinsus chesapeaki and P. andrewsi (Burreson et al 2005). Ribosomal DNA sequence variation has previously been used to discriminate between toxic and non-toxic strains of Alexandrium tamarense and Pseudonitzschia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include the phylogenetic position of Marteilia refringens (Berthe et al 2000), Pfiesteria shumwayae (Litaker et al 2005), and the phylogenetic synonymization of Perkinsus chesapeaki and P. andrewsi (Burreson et al 2005). Ribosomal DNA sequence variation has previously been used to discriminate between toxic and non-toxic strains of Alexandrium tamarense and Pseudonitzschia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Protozoan parasites in the phylum Paramyxea have been extensively studied in areas in which oysters and mussels are commercially raised (Becker & Pauley 1968, Wolf 1977, Figueras & Montes 1988, Villalba et al 1993, Fuentes et al 1995, Renault et al 1995, Camacho et al 1997, Berthe et al 2000, Hine & Thorne 2000. The presence of the ovarian parasite Marteilioides chungmuensis (Comps et al 1986) has been reported from oyster culture grounds in Korea (Chun 1970(Chun , 1972(Chun , 1979 and in Japan (Imai et al 1968, Matsusato & Masumura 1981.…”
Section: Abstract: Crassostrea Gigas · Gonad Development · Marteiliomentioning
confidence: 99%
“…All paramyxids are parasitic organisms of marine invertebrates. Although a relationship with haplosporidian species was suggested, any phylogenetic relationships with described species have been not confi rmed yet (Berthe et al 2000 ;Reece et al 2004 ), leaving the phylogenetic position of paramyxids under controversy.…”
Section: Marteiliamentioning
confidence: 96%